STATISTICAL EVALUATION OF COMPOSITIONAL DIFFERENCES BETWEEN UPPER EOCENE IMPACT EJECTA LAYERS - Marchand E.; Whitehead J. (My University, 2002)
Melt droplets formed by the impact of a large meteorite impact event(s) have been found in upper Eocene marine sediments from the Atlantic, Pacific, and Indian oceans. The number of discreet impacts that occurred to form these melt droplets can be gleaned by compositionally analysing the droplets and establishing the number of distinct groups. Previous studies have inferred two, three, or more source impact events, although we believe the statistical techniques used to distinguish the groupings are open to criticism. Multivariate and univariate analysis (including discriminant analysis) of the major-element composition of an increased data set of impact melt ejecta droplets have been performed. The results demonstrate that the uppermost ejecta layer is geochemically distinct from other late Eocene melt ejecta. Our statistical analysis suggests two underlying, purportedly stratigraphically separate ejecta layers, possess minimal differences that cannot be distinguished clearly from one another by discriminant analysis, which adds to the plausibility that they have a common source. Finally, our results reveal apparent disparities between the new major-element data from this study and data compiled from existing sources.
Keywords: microtektite; microkrystite; multivariate analysis; compositionalmeans; discriminant analysis; Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен